2013
DOI: 10.4314/ajcem.v14i3.7
|View full text |Cite
|
Sign up to set email alerts
|

A profile of wound infections in National Hospital Abuja

Abstract: Background: Wound Infections cause prolonged hospital stay, increased costs and also can result in increased patient morbidity and mortality. The current spread of multi-drug resistant bacteria has further heightened the need for regular bacteriological review of infected woundsand regular antibiotics surveillance studies so as to avoid the unguidedempirical treatment of wound infections which is quite common in this environment Aim: To determine the distributionof theisolates from wound specimens submitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
4
18
1
Order By: Relevance
“…The high rate of growth was found to be in indoor patients (54.9%) than OPD patients (38.8%) and emergency patients (20.3%), which was similar to the study of Iregbu et al (2013). The reason for the high prevalence in ward may be due to factor associated with acquisition of nosocomial pathogens in patients with recurrent long term hospitalization, complicating illness, prior administration of antimicrobial agents.…”
Section: Prevalence Of Mdr P Aeruginosasupporting
confidence: 81%
See 2 more Smart Citations
“…The high rate of growth was found to be in indoor patients (54.9%) than OPD patients (38.8%) and emergency patients (20.3%), which was similar to the study of Iregbu et al (2013). The reason for the high prevalence in ward may be due to factor associated with acquisition of nosocomial pathogens in patients with recurrent long term hospitalization, complicating illness, prior administration of antimicrobial agents.…”
Section: Prevalence Of Mdr P Aeruginosasupporting
confidence: 81%
“…In our present study, out of total bacterial isolates, 70.6% were Gram negative and 29.4% were Grampositive bacteria. In a similar study conducted by Giri et al (2008), Iregbu et al (2013), Eselbelhie et al (2013) Gram negative bacteria were found predominant. Most of the hospital-based studies nowadays show that Gram-negative bacteria was more prevalent than Gram-positive bacteria.…”
Section: Prevalence Of Mdr P Aeruginosamentioning
confidence: 54%
See 1 more Smart Citation
“…Such factors includes: the type and location of the wound, the depth and level of tissue perfusion, and the host immune response (3). In most instances, wound colonization is polymicrobial involving numerous microorganisms that may be pathogenic (7,8,9). Infected wound has actively multiplying pathogenic organisms with clinical signs of infection such as pain, redness, oozing of pus and yellowing of the wound site.…”
Section: Introductionmentioning
confidence: 99%
“…Several species of microbes have been reported in wound infection (Thanni et al, 2003;Shittu et al, 2002;Okesola and Kehinde, 2008;Obi, 2015;Muhammad et al, 2014;Iregbu et al, 2013;Gadzama et al, 2007). Sensitivity profile has been widely carried out on the pathogens found in wound infections (Taiwo et al, 2002;Obi, 2015;Iregbu et al, 2013). The level of microbial infestation with regard to diversity and density also influence the wound healing rate.…”
Section: Introductionmentioning
confidence: 99%